Community-Based Narcotics Prevention: An Effective Approach Towards Youth Drug Abuse Mitigation - Fransina S Latumahina; Anshari Betekeneng; Dandi Alvian Hakim; Arman Wally; Ari Fisal Waelissa (Universitas Muhammadiyah Sidoarjo, 2023)
This study focuses on the escalating issue of narcotics misuse and its deleterious effects on health, families, and society, emphasizing the role of preventive socialization in addressing this crisis. Utilizing a community-based approach, Leihitu District KKN students implemented a